Solitary Waves of 1-Nonlinear Schrödinger Equation in the Composite Right- and Left-Handed Metamaterial (Journal of Partial Differential Equations, 2020)
In this article, we analyze solitary waves in nonlinear left-handed transmission line with nonlinear diodes (Schottkys) which is an important issue, especially forsoliton devices. By applying the Kirchhoffs laws and reductive direct method, thevoltage in the spectral domain was obtained. Considering the Taylor series arounda certain modulation frequency, we obtained one dimensional Nonlinear Schrödinger Equation (NSE), which support envelops soliton, and bright soliton solutions. Usingsine-cosine mathematical method, soliton solutions of the standard Nonlinear Schrödinger equation are obtained. The method used is straightforward and concise and canbe applied to solve further of nonlinear PDEs in mathematical physics.
Keywords: CRLH transmission line; nonlinear Schrödinger equation; Sine-Cosine method; solitary waves.